Effects of low-dose combined olanzapine and sertraline on negative and depressive symptoms in treatment-resistant outpatients with acute exacerbated schizophrenia - Lang, Xiaoe; Zang, Xiaocui; Yu, Feng; Xiu, Meihong (Frontiers in Pharmacology, 2023)
Background: Treatment-resistant schizophrenia (TRS) is a major clinical challenge. Current antipsychotic medications do not adequately address negative and depressive symptoms in patients with TRS, and novel treatments are thus needed. This study examines the efficacy of low-dose combined olanzapine (OLA) and sertraline on depressive and negative symptoms in patients with TRS. Methods: A total of 34 TRS outpatients with acutely exacerbated schizophrenia were randomly assigned to OLA monotherapy (12.5–20 mg/day) (control group) or low-dose combined OLA (7.5–10 mg/day) and sertraline (50–100 mg/day) (OS group). Clinical symptoms were assessed using the Positive and Negative Syndrome Scale (PANSS) at baseline and at the end of treatment in weeks 4, 8, 12, and 24. Depressive symptoms and social functioning were also assessed. Results: Compared to the control group, the OS group showed significant improvements in depressive and negative symptoms over time. In addition, the low-dose combination of OLA and sertraline significantly improved social functioning compared with OLA monotherapy. There were no significant between-group differences in psychotic symptom improvement. However, the reduction in Hamilton Depression Rating Scale total score and PANSS negative subscore were not associated with improvements in social functioning, suggesting that these effects of combined treatment are independent. Conclusion: Low-dose combined OLA and sertraline may be effective in the treatment of negative and depressive symptoms compared with standard OLA monotherapy in patients with TRS who are experiencing an acute exacerbation of schizophrenia. Clinical Trial Registration: [ClinicalTrials.gov], identifier [NCT04076371].